Rating One Stop Wedding Center Website - Lim, Hui Sin (Universiti Malaysia Sarawak, (UNIMAS), 2020)
Wedding ceremony is an event where the bride groom shows to their family and friends that they are getting married and their families have combined to become one family. They are finally be readied to step to their next level of life which is marriage. However, it is not easy to prepare a wedding ceremony. Many people face problems during their preparation. They don’t know where to start their preparation and they don’t know which services should be chosen. They need to go from one boutique to another until they find the boutique that can fulfil their requirements. One Stop Wedding Center website provides a list of vendors that handles wedding preparation. This project focuses on the rating system of the wedding website. Rating system is used to generate top list of vendors which brings reference to the user as the ratings can reflects the popularity, quality of service and performance of the vendors. The objective of this project is to study the wedding style that is interested by users based on the ratings while providing a platform for vendors to promote their services. With this rating system, it is considered as a success when a well-functioned rating system is developed for One Stop Wedding Center website. Based on the ratings given by other users in this website, this helps customer to select the correct wedding vendors with the best quality services. For vendor side, they can know the customers’ satisfaction and make improvement to provide better services.